MORPHOLOGICAL RESPONSE OF BITTER ALMONDS (PRUNUS AMYGDALUS) TO NITROGEN NANO-FERTILIZER IN EARLY STAGES OF GROWTH - Badran, A; Savin, I Y (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii︠a︡ agronomii︠a︡ i zhivotnovodstvo, 2017)
The use of large quantities of chemical fertilizers caused in many harmful to humans, animals and the environment. Adding to that, the difficulty of using nitrogen fertilizers especially urea and loss a large amount of it in sandy soil (70%) by leaching. In the other side, using of nano-particles and nano-powders, can produce controlled or delayed releasing fertilizers. This strategy could be reduced leaching of fertilizers as the release occurs gradually and continuously. Hence, this experiment was conducted to study the effect of nano-fertilizer on morphological response of bitter almond rootstock at germination period and the first stages of growth compared to other chemicals fertilizers. The nuts were soaked in dis-tilled water for 48 hours. Subsequently, the seeds were sown in perlite and treated with different concen-trations of nano-fertilizer, urea and ammonium sulfate at 0%, 25%, 50% and 100% for each, then stratified at 6 C for 8 weeks. After cold stratification, non-germinated seeds were exposed to 22 C for three weeks to promote germination. Germinated seeds were sown in pots with a mixture of peat and perlite. The treatments were arranged in a randomized complete block design in factorial experiment with 3 repli-cates and 25 seeds for each replicate. The results revealed that, nano-fertilizer affected significantly on seed germination and first stages of bitter almond growth. Whereas, pre-treating seeds of bitter almond rootstock with 50% of nano-fertilizer positively increased germination measurements; germination per-centage, germination rate and index due to enhancing the amount of water that penetrates inside the seeds during the germination period which in turn improved the biological activity of stored food thus in-duced embryo to germinated early. Added to that, nano-fertilizer markedly increased stem length and diameter with producing stronger seedlings which had the tallest and deepest underground parts as well as length of primary and secondary roots/plant and number of secondary roots/plant. It can be attributed to that; nano-fertilizers are available for absorption and can provide all nutrients that required for plant growth throughout its slow release of fertilizer therefore reduce nitrogen fertilizer lost by leaching and elevate nitrogen utilization efficiency by plant comparing to other nitrogen fertilizers that are lost about 70% of its nitrogen content by leaching.